Electronic Effects on Chiral NHC–Transition-Metal Catalysis - Yong, Xuefeng; Thurston, Ryan; Ho, Chun-Yu (Synthesis, 2019)
Though the properties of N-heterocyclic carbenes (NHCs) are generally dominated by the very strong σ donating character, electronic activation has emerged as an effective method to cooperate with typical carbon-framework steric optimization for highly enantioselective chiral NHC–transition-metal catalysis in recent years. NHC electronic changes associated with structural variations are now better understood by quantitative analysis using various methods. Here we highlighted and correlated some interesting chiral induction improvement methods, which were brought by electronic and steric cooperation on chiral NHC–transition-metal catalysis.1 Introduction2 Hemilabile Sidechains on NHC Ligands3 Electronic and Bond Angle Changes Brought by NHC Core Size Variations4 Electronic Activators on the NHC Core5 Conjugated Systems and Fused Ring Structures6 Remote Electronic Activators on the N-Aryl Ring7 Summary and Outlook
Keywords: electronic effect; chiral N-heterocyclic carbenes; transition-metal catalysis; enantioselective synthesis